"Born for Universal Sway:" Women and Performance Culture in Boston, 1785-1860 - Futhey, Emma. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Drama.; Advisor: Heather Nathans.; Committee: Barbara Grossman, Jennifer Burton, and Bethany Wood.; Keywords: Theater history, Women's studies, and American history.